The activity of signal crayfish (Pacifastacus leniusculus) in relation to thermal and hydraulic dynamics of an alluvial stream, UK - Johnson, Matthew F.; Rice, Stephen P.; Reid, Ian (Springer, 2014)
Signal crayfish (Pacifastacus leniusculus) are an invasive species of global significance because of their detrimental impacts on freshwater environments and native organisms. The movement of signal crayfish was continuously monitored for 150-days through a 20-m reach of an alluvial stream in the UK. Passive integrated transponder-tags were attached to crayfish, allowing their location to be monitored relative to 16 antennae which were buried beneath the river bed. The activity of crayfish was related to water depth and temperature, which were continuously monitored within the instrumented reach. Crayfish were highly nocturnal, with less than 6% of movements recorded during daylight hours. Activity declined from September and was minimal in November when water temperature was low and flow depth was high. However, relations between environmental parameters and crayfish activity had poor explanatory power which may partly reflect biological processes not accounted for in this study. Water depth and temperature had a limiting relationship with crayfish activity, quantified using quantile regression. The results extend existing data on signal crayfish nocturnalism and demonstrate that, although signal crayfish can tolerate a range of flows, activity becomes limited as water temperature declines seasonally and when water depth remains high in autumn and winter months.